2016
DOI: 10.31235/osf.io/r4ghb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unfolding the Space Between Stars: Anthropology of the Interstellar

Abstract: In this anthropological account of the “interstellar” – the vast expanses of outer space between the stars – I take interstellar travel as an object of ethnographic study. First, I examine three interstellar space projects: NASA’s Voyager 1 spacecraft; 100 Year Starship’s manifesto on their quest to travel to another star; and SETI’s search for life in the universe. Finally, I turn to corresponding examples of interstellar travel in speculative fiction.In 2013, NASA announced a transmission from the Voyager 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Faced with these issues, some anthropologists have suggested that we turn to speculative fiction—and, specifically, science fiction, as a way of modelling the kinds of ‘extrapolations, intensifications, and mutations’ (Wolf‐Meyers, 2019, p. 19) that we might expect (see similarly Collins, 2021). 2 Such a turn allows for the thinking of scales and gulfs that are otherwise beyond anthropological ken (see Oman‐Reagan, 2015). It certainly has an appeal in a ‘scenario planning’ (Faubion, 2016) sort of way.…”
Section: A Posthuman Horrormentioning
confidence: 99%
“…Faced with these issues, some anthropologists have suggested that we turn to speculative fiction—and, specifically, science fiction, as a way of modelling the kinds of ‘extrapolations, intensifications, and mutations’ (Wolf‐Meyers, 2019, p. 19) that we might expect (see similarly Collins, 2021). 2 Such a turn allows for the thinking of scales and gulfs that are otherwise beyond anthropological ken (see Oman‐Reagan, 2015). It certainly has an appeal in a ‘scenario planning’ (Faubion, 2016) sort of way.…”
Section: A Posthuman Horrormentioning
confidence: 99%
“…An ontological approach challenges dualist distinctions to suggest there are not only different world views, but may be different worlds. Such conceptual shifts are helpful as we attempt to imagine and relate to an ETI experience of the universe in which "the world" may look, feel, and act entirely different due to differences in biology, mind, or culture [31]. Recent anthropology also offers "extraterrestrial relativism" [17] and other non-anthropocentric ways of thinking about existence through different natures, minds, and experiences.…”
Section: Ontological Anthropologymentioning
confidence: 99%
“…Historian of science Colin Milburn makes a compelling argument that science fiction can function as a "repository of modifiable futures" in science (Milburn, 2010). Some science fiction thus provides opportunities for fruitful speculation about extraterrestrial intelligence beyond classic anthropocentric assumptions and helps us to think about alternative possible futures (Collins, 2008;Oman-Reagan, 2015b). The "exercise of imagination," Ursula K. Le Guin reminds us, "has the power to show that the way things are is not permanent, not universal, not necessary" (Le Guin, 2004).…”
Section: Imagining Futures Otherwisementioning
confidence: 99%